Investigation on rheological performance of indigenously developed sustainable low clinker hybrid cementing binders - K. Gowri; A. Abdul Rahim (Results in Engineering)
Cement production is a chief source of greenhouse gas emissions and is responsible for 5–8 % of anthropogenic CO2 emissions to the atmosphere worldwide. Incorporating Supplementary cementitious materials (SCMs) into cement production can lessen the need for parent materials and also reduce about 30 % of carbon dioxide (CO2) footprint. This study examines the rheological performance of the indigenously developed low-clinker hybrid cementing binders. The rheological behavior of blends could vary with different factors like the quantity of cement replacement, the type of mineral additive, the water-to-binder ratio, and the age of the paste. The rheological performance was learned through flow curves, constant shear rate, and small amplitude oscillatory shear tests. The results obtained from samples revealed that the binary blended (BB) mix exhibited higher shear stress, and the ternary (TB) and quaternary blends (QB) exposed low shear stress. From the analysis, the dynamic yield stress was increased by increasing the SCM proportion. Constant shear rate test results showed that the BB has the highest static yield stress, then other blends. Samples showed significant elasticity and linear viscoelasticity region. The resulting compressive strength of 28 days of curing showed that the quaternary mix QB1 had the highest ultimate compressive strength (52 MPa) increased by 101.9 %. While the BB has shown the least strength (80.3 %) among other blends. The characterization studies were opted to identify the properties of SCMs. The morphological study was conducted to recognize the effect of SCMs leading to the formation of denser structures to enhance compressive strength.